The important factor of construction site management: Case study of doubles storey bungalow project Darulaman Lakehome Phase 2 / Nadzirah Nasir - Nasir, Nadzirah (Universiti Teknologi MARA, Perak, 2015)
The construction industry has been built on the need to economic growth and provides a lot of opportunities. Site management is a very important in construction project, where it includes of the planning, control and coordination of the project. These are the most important factor in the site management and will cause many problems happen in the construction project if it not delivered properly. This is due to the contractor or management team do not have the capacity of technical know-how, lack of experience and site management skill in the related project. The main purpose of this study is to identify the important factor of site management for the project at Lakehome phase 2 Bandar Darulaman. From observation through the practical training, the aspect of site management that can contribute to the delay or uncompleted project such as cost, time, supplier and manpower. Hence, cooperation from all parties between client, contractor and local authorities will minimize the problem of site management in the construction project.